Grain size properties of estuary sediment from Aceh Jaya, Aceh - Muhammad Arif Nasution; Rudi Hermi; Heriansyah Heriansyah; Friyuanita Lubis; Mira Mauliza Rahmi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
This study aimed to determine the sediment grain size distribution in four estuary locations in Aceh Jaya (Kuta Tuha, Lhok Geulumpang, Krueng No, Keude Unga). These findings will contribute to our understanding of sediment dynamics in estuarine environments and inform management strategies for these critical coastal habitats. The methods used in this study, such as mean, sorting, skewness, and kurtosis, and determination of sediment textural with ternary plot, were used to determine the sediment grain size distribution. In Addition, it will examine the relationship between sediment grain size composition and spatial distance to mouth bar using the Spearman correlation. Composition sediment at all locations dominated by fine sand. Grain size variations (26.735 198.709 m) show that at all locations mainly consists of very fine sand whereas at Kuta Tuha combination of fine sand and medium sand. The variations of sorting (1.193 2.59), skewness (-0.625 0.876) and kurtosis (0.46 6.883) indicate moderately sorted, very coarse skewed, and very platykurtic sediments. Textural sediment classified as sand, silty sand, and very slightly silty sand. We also found positive correlation between spatial distance from mouth bar and sediment composition. These findings will contribute to our understanding of sediment dynamics in estuarine environments and inform management strategies.Keywords:Sediment grain distributionTextural of sedimentAceh Jaya EstuarySortingSkewness